ASSESSMENT OF NURSING TEACHERS ́ ABILITIES TO FACILITATE ADULT LEARNING - Patricia Bover Draganoc; Maria Cristina Sanna (Universidade Federal do Paraná, 2015)
The aim of this study was to evaluate the performance that the nursing teacher assigns for himself, in his abilities as facilitator for adult ́s learning. It was a descriptive, comparative, transversal and quantitative study developed with 226 nursing teachers from the nursing graduation in São Paulo. Data were collected from June 2010 to February 2011, with the Likert scale, launched in Excel® spreadsheet and analyzed using descriptive statistics and non-parametric Wilcoxon and Friedman tests. Teachers considered themselves being far from the highest level of abilities they wanted to achieve, and they said having greater control to the design and implementation of learning experience that the conceptual and theoretical references of adult learning. Teachers considered themselves having less than the ideal abilities to facilitate learning.